Long Term Clinical Prognostic Factors in Relapsing-Remitting Multiple Sclerosis: Insights from a 10-Year Observational Study. - Gabriel Bsteh; Rainer Ehling; Andreas Lutterotti; Harald Hegen; Franziska Di Pauli; Michael Auer; Florian Deisenhammer; Markus Reindl; Thomas Berger (PLoS ONE, 2016)
Multiple sclerosis (MS) has a highly heterogenic course making prediction of long term outcome very difficult.The objective was to evaluate current and identify additional clinical factors that are linked to long term outcome of relapsing-remitting MS assessed by disability status 10 years after disease onset.This observational study included 793 patients with relapsing-remitting MS. Clinical factors hypothesized to influence long term outcome measured by EDSS scores 10 years after disease onset were analysed by Kaplan-Meier-estimates. Multinomial logistic regression models regarding mild (EDSS ≤2.5), moderate (EDSS 3.0-5.5) or severe (EDSS ≥6.0) disability were calculated to correct for confounders.Secondary progression was the strongest predictor of severe disability (Hazard ratio [HR] 503.8, 95% confidence interval [CI] 160.0-1580.1); p<0.001). Complete remission of neurological symptoms at onset reduced the risk of moderate disability (HR 0.42; CI 0.23-0.77; p = 0.005), while depression (HR 3.59; CI 1.14-11.24; p = 0.028) and cognitive dysfunction (HR 4.64; CI 1.11-19.50; p = 0.036) 10 years after disease onset were associated with severe disability. Oligoclonal bands and pregnancy were not correlated with disability.We were able to identify clinically apparent chronic depression and cognitive dysfunction to be associated with adverse long term outcome in MS and to confirm that pregnancy has no negative impact. Additionally, we emphasize the positive predictive value of complete remission of initial symptoms.